Unsustainability of recommended fertilization rates for coffee monoculture due to high N2O emissions - Capa Mora, E. (2015)
Industrial fertilization with an excess of mineral fertilizer leads to water pollution and global warming. For instance, high mineral fertilization rates in coffee plantations of Ecuador result in N losses, such as emissions of N2O, a greenhouse gas to the atmosphere. Therefore, we conducted here field experiments to optimize fertilization. We studied the effects of mineral fertilizers on soil fertility, N2O emissions, productivity, and profitability of monoculture coffee systems in Loja, Ecuador. During 2 years, treatments on plots of Coffea arabica included (1) low fertilization with 70 N, 22 P, and 31 K kg/ha/year first year and then 200 N, 65 P, and 62 K second year; (2) medium fertilization with 150 N, 44 P, and 62 K first year and then 300 N, 87 P, and 125 K second year; (3) high fertilization with 225 N, 65 P, and 93 K and then 400 N, 109 P, and 187 K second year; and (4) control plots without fertilizers. Results showed that, although medium-high fertilization rates recommended by experts gave high coffee yields and income, such treatments produced high N2O emissions and thus led to low production/N2O emissions ratios of 208 for medium fertilization, and of 188 for high fertilization. Low fertilization gave a high production/N2O ratio of 603, and an income of 7606 USD/ha higher than control, of 3524 USD/ha. Our findings demonstrate that rates based on expert recommendations from local extension services and usually applied by Ecuadorian coffee growers, such as our medium rate, fail to achieve a sustainable production. The application of approximately half the expert recommended rates, such as our low treatment, could allow an environmental and economic sustainability in monoculture coffee plantations of Ecuador. © 2015, INRA and Springer-Verlag France.